PENGEMBANGAN LKS PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN BERBASIS PENDEKATAN INKUIRI DI SMA NEGERI 1 CANDUANG - Ennike Gusti Rahmi (Unika Santu Paulus Ruteng, 2018)
The purpose of this research is to produce valid and pratical student worksheet on the material structure and function of plant tissue based on inquiry approach of class XI science SMA Negeri 1 Canduang. The types of this research is a development research. The models was developed by using three stages from 4-D models is such as define, design, develop, and disseminate. The disseminate phase is not done because of limited time and expense in the research. Data instrument are used such as validation sheet and practicality. Based on the research that has been made known the student worksheet be valid with percentage 80.27%. Practicality of LKS is obtained from teachers with percentage 75% and students practical with percentage of 85.17%. Thus the quality of the products can be said to be valid by the validity of the test results of that has been done and practical by the practicality of the result of that has been done.